Neurodidactic teacher training program for educational dropouts in vulnerable groups - De Barros Camargo, Claudia; Flores Melero, Carmen; Pinto Díaz, Cristina; Marín Perabá, Cristina (Frontiers in Education, 2023)
Neuroeducation is presented as an effective teaching tool for the construction of an equitable society, 1regardless of the population to which it belongs. The most vulnerable groups will be supported by this educational methodology, which has been introduced very recently in teacher training. The role of the teacher according to the neurodidactic, is to create a process of synapses in the neuronal structures, through activities that the subject finds innovative, attractive and motivating. To do this, its is necessary to know what aspects must be given in the training of teachers/ as involved with students belonging to vulnerable groups, to be able to develop intervention programs that are effective, based on neurodidactics or neuroeducation. The study population is taken into account by the responses of the University of Jaen (UJA) higher education teachers, to whom a Likert scale is passed, performed through an operationalization table, to know the degree of knowledge you have about neuroscience, more specifically about neuroeducation. Likewise, they will be asked about the characteristics that they consider essential for neurodidactics to be effective, that is, the right way to get the synapse in the brain development of students.